Infant death from accidental suffocation and strangulation in bed in England and Wales: rare or unrecognised events? - Joanna Jane Garstang; Marivjena Menka (BMJ Publishing Group, 2024)
Background Mandatory joint police and healthcare investigations of sudden unexpected death in infancy (SUDI) have been in place since 2008 in England. These include death scene examination with cause of death determined at multiprofessional case conference. Detailed evidence on sleep arrangements is available for most cases potentially leading to more being identified as due to accidental suffocation. SUDI remaining unexplained following investigation are classified as SIDS (sudden infant death syndrome) or unspecified deaths.Our objective was to determine whether detailed SUDI investigation has led to an increase in deaths classified as accidental suffocation or strangulation in bed (ASSB)?Methods We obtained official mortality data for England and Wales for infants dying aged 0-364 days for International Statistical Classification of Diseases and Related Health Problems, 10th revision codes R95 (SIDS), R96, R98, R99 (unspecified causes of mortality) and W75 (ASSB) for the years 2000-2019.We calculated the mortality rate for ASSB, SIDS and unspecified causes based on total live births each year.Results Unexplained SUDI decreased from 353 in 2000 to 175 in 2019, with the mortality rate falling from 0.58 to 0.29 per 1000 live births. The total postneonatal mortality rate fell during this time from 1.9 to 0.9 per 1000 live births suggesting this is a genuine fall. SIDS accounted for 70% of unexplained SUDI in 2000 falling to 49% in 2020 with a corresponding increase in R99 unspecified deaths.Few deaths were recorded as ASSB (W75), ranging between 4 in 2010 and 24 in 2001. The rate for ASSB ranged from 0.6 to 4.0 per 100000 live births.Conclusions There is a shift away from SIDS (R95) towards unspecified causes of death (R96, R98, R99). Improved investigation of deaths has not led to increased numbers of death identified as due to ASSB. There needs to be clear guidelines on accurate classification of deaths from ASSB to facilitate learning from deaths and inform prevention efforts.